Analysis of the Differences in Unit Costs for Bronchopneumonia Services Based on Clinical Pathway with INACBGs Rates and Hospital Rates at Dr. RSAL. Mintohardjo - Jack Steven Saripantung; Rokiah Kusumapradja; Intan Silviana (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Hospital is one of the health service facilities that tries to overcome the health service balance between investment costs and the availability of applicable unit costs. Calculation of unit costs has an important role, including being used for budget planning, cost control, subsidies and as information in decision making. In the era of National Health Insurance (JKN) in Indonesia, Hospitals that cooperate with the Social Security Administering Agency (BPJS) Health are paid using the Indonesian Case Base Groups (INACBGs) package system. The acquisition of claim payments at Dr. Mintohardjo Naval Hospital according to the INACBGs rate compared to Hospital costs has a negative difference value for Bronchopneumonia cases. The purpose of this study was to analyze the difference in unit costs of Bronchopneumonia services based on Clinical Pathway towards the determination of INACBGs Rates and Hospital Rates at Dr. Mintohardjo Naval Hospital. This type of research is quantitative, comparative analytical observation using a cross-sectional research design according to the Hospital perspective. The subjects of the study were Medical Records and BPJS Kesehatan claim files for Bronchopneumonia services for the period April to September 2023, totaling 61 files. The study was conducted from January 2024 to April 2024. Data analysis used the paired t-test statistical method in the statistical test application (SPSS Version 26). The results of the study on calculating unit costs using the Activity Based Costing (ABC) method are as follows: 1) There is a difference between the calculation of unit costs with INACBGs rates of negative 6.2% and unit costs with Hospital rates of positive 11.2%, 2) There is a difference in the unit cost of Bronchopneumonia services based on Clinical Pathway with the Activity Based Costing method against INA-CBGs Rates, 3) There is a difference in the unit cost of Bronchopneumonia services based on Clinical Pathway with the Activity Based Costing method against Hospital Rates. The suggestions in this study are: 1) For the financial management of RSAL Dr. Mintohardjo to improve competence in calculating unit cost rates for services based on clinical pathways with the Activity Based Costing method, one of which is through training, 2) Updating and conducting clinical pathway audits periodically, 3) Re-evaluating hospital rates to increase the margin of each service so that the margin obtained is in accordance with what has been set, 4) Digitizing patient usage data that was previously still written manually to avoid errors in entering details of service costs.